A murder for the sages - Lillard, Amy (Lillard, Amy. Sunflower Café mysteries., 2024)
"The unusual death of local herb farmer, Ginger Reed, is the talk of Yoder. Naturally, Sissy is intrigued. The official report classifies Ginger's demise as an accident, concluding that she ran herself over with a tractor. But Sissy's cousin, Naomi, a friend and longtime employee of Ginger's, insists that's impossible. When she asks for Sissy's help in unearthing the truth, Sissy's on the case--accompanied as ever by her loyal Yorkie companion, Duke ... The deeper Sissy digs, the longer the list of suspects grows--and none of them are Ginger. Near the top is Ginger's resentful sister-in-law, Mallory. Next is Naomi's brother, Lloyd, who's bitter about the oil derrick presumably pumping black gold from Ginger's land--land that once belonged to his family. Naomi herself could be a suspect--it's her tractor, after all. But the investigation stalls when Naomi makes a shocking turnaround in her story. Is she lying? And if so, why? Then a missing dog, a desperate lawyer, and a teenage con artist are added to the mix, and the puzzle becomes hopelessly complicated. If Sissy doesn't solve it quickly, she'll be lost in the weeds as a killer reaps a deadly harvest ..."--